Accounting Knowledge and Skill Development of Cooperative Employees in Chiangmai Province - Yeesoonsam, Kirana; Tarapituxwong , Supareuk; Tanniyom, Kanta; Ramingwong, Palinda (Community and Social Development Journal, 2022)
This research was a qualitative research that used in-depth interviews and purposive sampling by convenience sampling, for categorizing problems, analyzing associations, an analysis of changes in accounting record accuracy and quantitative research; using a questionnaire to assess knowledge and understanding of the participants before and after the training, as well as a developmental assessment form to check the accuracy of accounting preparation of cooperative employees both before and after the workshop, research aimed at improving accounting knowledge for cooperative employees in Chiang Mai and cooperative stakeholders to create transparency and reduce social inequality. Therefore, the research team summarized the issues of the study, divided into 2 parts as follows: the results of the first part of the study show the results of the development of accounting skills and professional ethics of 800 cooperative employees in Chiang Mai, and it found that the participants’ scores on knowledge and understanding of accounting after the training increased by 12.34. Moreover, From the workshops and practical trials, it was found that cooperative employees were able to record accounts and prepare financial statements correctly after additional training; from the accuracy score of 30 percent to 65 percent, which represents the ability to prepare accounts more accurately for 35 percent. For the second part, the results of the training to develop knowledge and understanding about the cooperative system of 500 stakeholders showed that their knowledge and understanding increased by 15.60%. In addition, there was an economic valuation of the research project’s worthiness conducted for the future allowance valuation method, in which the result of the study found that the economic value for the accounting skill development was 1,659,660.50 baht.